Pharmacokinetic Study of Frovatriptan Succinate Tablet After Single and Multiple Oral Doses in Chinese Healthy Subjects - Zheng H; Xia Y; Qu S; Fan L; Zhang J; Ma Z; Chen Y; Fan H (Dove Medical Press, 2021)
Hongquan Zheng,1,2 Yan Xia,3 Shengjun Qu,4 Lin Fan,2 Jingjing Zhang,1 Zhixiang Ma,1 Yangsheng Chen,4 Hongwei Fan1,2 1Department of Clinical Pharmacology Lab, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, People's Republic of China; 2School of Basic Medicine and Clinical Pharmacy, China Pharmaceutical University, Nanjing, Jiangsu, People's Republic of China; 3Jiangsu Leeway Biological Technology Co., Ltd, Nanjing, Jiangsu, People's Republic of China; 4CP Pharmaceutical Qingdao Co., Ltd, Qingdao, Shandong, People's Republic of ChinaCorrespondence: Hongwei FanNanjing First Hospital, Nanjing Medical University, 68 Changle Road, Nanjing, 210006, People's Republic of ChinaTel +86 25 5288 7030Fax +86 25 5288 7031Email fanhongwei178@sina.comYangsheng Chen 3601 Tuanjie Road, Economic and Technological Development Zone, Qingdao, People's Republic of ChinaTel +86 18766396996Email chenys@cppqd.comPurpose: The present report describes findings from a Phase I clinical study that evaluated the single- and multiple-dose pharmacokinetics of frovatriptan succinate tablet in Chinese healthy subjects.Methods: A total of 24 healthy subjects were enrolled. In single-dose study, 2.5, 5, and 10 mg oral doses of frovatriptan succinate tablet were administrated. A 2.5 mg frovatriptan succinate tablet was administrated 12 times in 7 days in the multiple-dose study. Blood samples were collected at scheduled time points.Results: The results in single-dose study indicated that the blood levels were proportional to the administered dose, with the mean Cmax and AUClast ranging from approximately 6.27 ng/mL- 17.35 ng/mL and 92.52 h⋅ng/mL - 287.40 h⋅ng/mL over the dose range. In the multiple-dose study, moderate drug accumulation was noted, which was attributable to forvatriptan's long t1/2 of about 26.47 to 30.63 h. Gender differences were noticed in both single- and multiple-dose study; exposure PK parameters were consistently higher in female than in male.Conclusion: These pharmacokinetic evaluations in healthy Chinese subjects found that frovatriptan succinate tablet has an acceptable pharmacokinetic profile in Chinese subjects.Keywords: frovatriptan succinate, pharmacokinetics, single-dose, multiple-dose